Screening, detection and management of delirium in the emergency department – a pilot study on the feasibility of a new algorithm for use in older emergency department patients: the modified Confusion Assessment Method for the Emergency Department (mCAM-ED) - Grossmann, Florian F (BioMed Central, 2014)
BACKGROUND: Delirium in emergency department (ED) patients occurs frequently and often remains unrecognized. Most instruments for delirium detection are complex and therefore unfeasible for the ED. The aims of this pilot study were first, to confirm our hypothesis that there is an unmet need for formal delirium assessment by comparing informal delirium ratings of ED staff with formal delirium assessments performed by trained research assistants. Second, to test the feasibility of an algorithm for delirium screening, detection and management, which includes the newly developed modified Confusion Assessment Method for the Emergency Department (mCAM-ED) at the ED bedside. Third, to test interrater reliability of the mCAM-ED. METHODS: This was a pilot study with a pre-post-test design with two data collection periods before and after the implementation of the algorithm. Consecutive ED patients aged 65 years and older were screened and assessed in the ED of a tertiary care center by trained research assistants. The delirium detection rate of informal ratings by nurses and physicians was compared with the standardized mCAM-ED assessment performed by the research assistants. To show the feasibility at the ED bedside, defined as adherence of ED staff to the algorithm, only post-test data were used. Additionally, the ED nurses’ assessments were analyzed qualitatively. To investigate the agreement between research assistants and the reference standard, the two data sets were combined. RESULTS: In total, 207 patients were included in this study. We found that informal delirium assessment was inappropriate, even after a teaching intervention: Sensitivity of nurses to detect delirium without formal assessment was 0.27 pretest and 0.40 post-test, whilst sensitivity of physicians’ informal rating was 0.45 pre-test and 0.6 post-test. ED staff demonstrated high adherence to the algorithm (76.5%). Research assistants assessing delirium with the mCAM-ED demonstrated a high agreement compared to the reference standard (kappa = 0.729). CONCLUSIONS: Informal assessment of delirium is inadequate. The mCAM-ED proved to be useful at the ED bedside. Performance criteria need to be tested in further studies. The mCAM-ED may contribute to early identification of delirious ED patients.